A Serum Marker for Early Pancreatic Cancer With a Possible Link to Diabetes. (6th October 2021) - Nam, Hoonsik; Hong, Soon-Sun; Jung, Kyung Hee; Kang, Sunmi; Park, Min Seok; Kang, Suyeon; Kim, Han Sun; Mai, Van-Hieu; Kim, Juyoung; Lee, Ho; Lee, Woohyung; Suh, Young Ju; et al.
Abstract: Background: Pancreatic cancer (PC) has a grim prognosis, and an early diagnostic biomarker has been highly desired. The molecular link between diabetes and PC has not been well established. Methods: Bioinformatics screening was performed for a serum PC marker. Experiments in cell lines (5 PC and 1 normal cell lines), mouse models, and human tissue staining (37 PC and 10 normal cases) were performed to test asprosin production from PC. Asprosin's diagnostic performance was tested with serums from multi-center cohorts (347 PC, 209 normal, and 55 additional diabetic patients) and evaluated according to PC status, stages, and diabetic status, which was compared with that of CA19-9. Results: Asprosin, a diabetes-related hormone, was found from the bioinformatics screening, and its production from PC was confirmed. Serum asprosin levels from multi-center cohorts yielded an age-adjusted diagnostic area under the curve (AUC) of 0.987 (95% confidence interval [CI] = 0.961 to 0.997), superior to that of CA19-9 (AUC = 0.876, 95% CI = 0.847 to 0.905), and a cut-off of 7.18 ng/mL, at which the validation set exhibited a sensitivity of 0.957 and a specificity of 0.924. Importantly, the performance was maintained in early-stage and non-metastatic PC, consistent with the tissue staining. A slightly lower performance against additional diabetic patients (n = 55) was restored by combining asprosin and CA19-9 (AUC = 0.985, 95% CI = 0.975 to 0.995). Conclusions: Asprosin is presented as an early-stage PC serum marker that may provide clues for PC-induced diabetes. Larger prospective clinical studies are warranted to solidify its utility.